GOVERNMENT SIZE AND ECONOMIC GROWTH IN TURKEY: A THRESHOLD REGRESSION ANALYSIS - Iyidogan, Pelin Varol; Turan, Taner (Univ Economics-Prague, 2017)
We examine the relationship between the government size and economic growth by using threshold regression model and quarterly data over the period 1998:1-2015:1 for Turkey. Our results provide a strong evidence for the existence of a non-linear relationship. The estimated threshold levels, as a percentage of GDP, are 16.5 for the government total expenditures, 12.6 for consumption expenditures and 3.9 for investment expenditures. We find that an increase in the government size leads to a significant rise (decline) in economic growth rate when the government size is below (above) the threshold level, confirming the predictions of Armey curve. Our findings have a clear policy implication: since the realized government consumption and total expenditures are well above the estimated threshold levels, a reduction in the government size would boost the growth rate.
Keywords: economic growth; government size; non-linearity; threshold estimations